Factors associated with phosphate homeostasis in children with beta-thalassemia major: An analytical cross sectional study from Pakistan - Lena Jafri; Arsala Jameel Farooqui; Bushra Moiz; Aisha Sheikh; Hafsa Majid; Sarah Nadeem; Ruhul Quddus; Samia Khan; Qurat-ul-Ain Khan; Aysha Habib Khan (PLoS ONE, 2025)
Introduction Children with beta-thalassemia major (β-TM) commonly experience metabolic bone diseases. Understanding fibroblast growth factor 23 (FGF-23) levels in these children can shed light on phosphate dysregulation. This study aimed to assess changes in phosphate homeostasis and associated factors, including FGF-23 and explore relationships between iron overload, FGF23 levels, and phosphorus regulation for clinical management of phosphate disorders, in children with β-TM. Methods 143 β-TM patients (57.3% male, median age 12 years) were recruited from Fatimid Foundation Karachi, a blood transfusion facility from January to October 2022. Clinical and biochemical evaluations were conducted at Aga Khan University Hospital, including serum ferritin, calcium (Ca), phosphate (P), vitamin D levels, and FGF-23. Descriptive and inferential statistics including multivariable analysis were applied. Results This study enrolled 143 patients, with 57.3% males. The median age was 12 years, with 53% underweight. Blood transfusion rates varied, with 66.4% receiving 2/month. Bone/joint pain was reported by 76.2%, with 60.8% requiring analgesics. Median serum ferritin was 2768.3 ng/mL. Hypophosphatemia and hyperphosphatemia were observed in 5.6% and 3.5% of participants, respectively. Vitamin D deficiency/insufficiency affected 92.3%. Plasma c-FGF23 was elevated in 60.8%, while i-FGF23 was high in 14%. A low TMP-GFR (glomerular filtration rate) was associated with high c-FGF23 and low i-FGF23. Multivariable regression revealed c-FGF23, TMP:GFR, Corrected Ca, iPTH, and an interaction term between corrected Ca and iPTH as predictors of serum P variability (~75%). Conclusion The study identified contributors to the variations observed in serum P levels in individuals with β-TM and recommends multidisciplinary care and prospective future studies to form targeted interventions for this population.